Penyuluhan Hukum Alas Hak Tanah dalam Penguatan Keamanan Hukum dan Pembangunan Ekonomi Desa Limbang Jaya II Kabupaten Ogan Ilir - Sarah; Syahriati Fakhriah; Syamsul; M Adi Saputra; Firdaus Akbar (KADARKUM: Jurnal Pengabdian Kepada Masyarakat, 2026)
The issue of land ownership without valid legal basis remains a critical problem in rural areas, including Limbang Jaya II Village, Ogan Ilir Regency. The low level of legal literacy among rural communities regarding land certification has led to a high potential for agrarian disputes, weak legal certainty, and limited utilization of land as a productive economic asset. This community service activity aims to enhance public awareness and legal understanding of the importance of legal land ownership as a means to achieve legal security and support local economic development. The methods employed include legal counseling, interactive discussions, dispute resolution simulations, and administrative assistance related to land certification. The results indicate a significant improvement in participants’ understanding of the types of land rights, land certification procedures, and the economic benefits of certified land. Moreover, this activity encourages active participation from both community members and village officials in establishing an orderly and sustainable land governance system. Therefore, legal counseling on land ownership rights has proven to be an effective preventive strategy against agrarian conflicts and a means of empowering rural communities based on legal certainty. Keywords: land ownership rights; legal certainty; rural community empowerment; legal counseling; land certification